Peace and justice: a limited reconciliation - Biggar, N (Kluwer Academic Publishers, 2002)
This paper aims to relax the tension between the political requirements of making peace and moral demands of doing justice, in light of the 'peace processes' in South Africa and Northern Ireland. It begins by arguing that criminal justice should be reconceived as consisting primarily in the vindication of victims, both direct and indirect. This is not to deny the retributive punishment of perpetrators any role at all, only to insist that it be largely subservient to the goal of vindication. Why should we take such an account of justice to be true? The paper offers two reasons. First, Christians - and even secularist liberals - have a prima facie reason in the consonance of this account with the Bible's eudaimonistic conception of justice as ordered to the restoration of healthy community. Second, since all concepts of criminal justice share the basic notion of putting right what is wrong, it would be odd if the repair of damage done to victims (i.e., their 'vindication') were not prominent among its concerns; and there are reasons to suppose that this vindication should actually predominate in relation to the other principles of justice (the retributive 'balancing' of crime and punishment, and the reform of the criminal for his own sake). In its final sections, the paper applies the proposed conception of criminal justice to the 'peace processes' in South Africa and Northern Ireland, and concludes that in both cases, notwithstanding concessions to the politics of peace-making, considerable justice has been done.